The interrupters every city needs its heroes - James, Steve; Kotlowitz, Alex; Matthews, Ameena; Bocanegra, Eddie (Dogwoof, 2012)
The Interrupters tells stories of three violence interrupters who try to protect their Chicago communities from the violence they once employed. The film's main subjects work for an innovative organization, CeaseFire. Founded by an epidemiologist who believes that the spread of violence mimics the spread of infectious diseases, and so the treatment should be similar: go after the most infected, and stop the infection at its source. One of the cornerstones of the organization is the violence interrupters program. The Interrupters--who have credibility on the streets because of their own personal histories--intervene in conflicts before they explode into violence
Dokumentarfilm
Keywords: Matthews, Ameena; Williams, Cobe; Bocanegra, Eddie; CeaseFire (Organization : Chicago, Ill.); Violence / Illinois / Chicago / Prevention; Conflict management / Illinois / Chicago; Community organization / Illinois / Chicago; Gang prevention / Illinois / Chicago; Gangs / Illinois / Chicago; Gangs -- Illinois -- Chicago.; Gang prevention -- Illinois -- Chicago.; Community organization -- Illinois -- Chicago.; Conflict management -- Illinois -- Chicago.; Violence -- Illinois -- Chicago -- Prevention.; Bande; Gewalt; Prävention; Stadtverwaltung; Chicago, Ill.; Film; DVD-Video